2022
DOI: 10.3847/psj/ac67a7
|View full text |Cite
|
Sign up to set email alerts
|

Global-scale Reshaping and Resurfacing of Asteroids by Small-scale Impacts, with Applications to the DART and Hera Missions

Abstract: We use a novel approach to model the entire cratering process resulting from impacts on small, weak asteroids that uses shock physics code calculations directly. We found that small-scale impacts (with a projectile size less than 1/150 of the target size) can significantly deform weak asteroids, causing global resurfacing at the same time. As a result, the collisional lifetime of the overall asteroid shapes is significantly lower than the traditionally used lifetime based on catastrophic disruption events. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…As rocks tend to be weaker with increasing size, it is possible that asteroids in the 1 km diameter range are already in the gravity-dominated regime (Asphaug et al 2002), as found with the SCI impact on Ryugu (Arakawa et al 2020). The DART impact on a cohesionless Dimorphos would be likely to produce morphologies that are dissimilar to simple cratering events and would change the global morphology of the asteroid (Raducan & Jutzi 2022).…”
Section: Impact Physicsmentioning
confidence: 99%
“…As rocks tend to be weaker with increasing size, it is possible that asteroids in the 1 km diameter range are already in the gravity-dominated regime (Asphaug et al 2002), as found with the SCI impact on Ryugu (Arakawa et al 2020). The DART impact on a cohesionless Dimorphos would be likely to produce morphologies that are dissimilar to simple cratering events and would change the global morphology of the asteroid (Raducan & Jutzi 2022).…”
Section: Impact Physicsmentioning
confidence: 99%
“…The corresponding orbital period change is ∼−200 s. This result indicates that even though Dimorphos's mass accounts for only ∼1% of the total system mass, if global deformation occurs, the mutual gravitational field is greatly modified, leading to a large orbital period change. Importantly, if Dimorphos experiences a global deformation, it implies that its structure is weak(Raducan & Jutzi 2022;Stickle et al 2022). Then, it is possible that the…”
mentioning
confidence: 99%
“…Raducan et al (2019) studied impacts on targets with cohesion between 0.1 and 100 kPa. However, due to the new evidence of very weak asteroid surfaces (e.g., Walsh et al 2019;Arakawa et al 2020), this study was extended by Raducan & Jutzi (2022) to impacts on targets with cohesion down to 0 Pa. They found that, when impacting a target with fixed, 40% porosity and f = 0.6, the β factor increases from ≈3.5 for a 50 Pa target to β ≈ 5 for a cohesionless 0 Pa target.…”
Section: Systematic Numerical Studies On the Influence Of Physicalmentioning
confidence: 94%
“…In Figure 1(a), the dotted lines show the total amount of ejecta mass that does not escape the Didymos system. As discussed in Raducan & Jutzi (2022), for impacts on strong targets (Y 0 > ≈50 Pa), most of the mass is ejected at speeds higher than the escape velocity of the Didymos system. The reason for this is that the ejected material must have a maximum speed that exceeds the escape velocity needed to overcome the cohesive strength of the target (Raducan et al 2019;Raducan & Jutzi 2022).…”
Section: Momentum Distribution In Ejectamentioning
confidence: 99%
See 1 more Smart Citation